Azimuthal variations in xylem structure and water relations in cork oak (Quercus suber) - Čermák, Jan; Barij, Nadia; Stokes, Alexia (IAWA Journal, 2011)
Keywords: hydraulic conductivity; sap; vessel lumina; wood anatomy

Vessel size and number are contributors to define wood density in cork oak - Leal, Sofia; Sousa, Vicelina B; Knapic, Sofia; Louzada, José Luís; Pereira, Helena (European Journal of Forest Research, 2011)
Cork oak (Quercus suber L.) has a dense wood that allows high-quality uses. In the present work, we study the inﬂuence of vessel characteristics, measured through image analysis and optical microscopy, on wood density, measured using X-ray microdensitometry, on 40-year-old trees. Vessel area increases with cambial age (5403–33064 lm 2 ), while wood density decreases (1.229–0.836 g/cm 3 ). The number of vessels is relatively constant at 6 vessels/mm 2 , while vessel proportion in cross-section increases from 3.3% near the pith to 20.5% near the bark. In growth rings closest to the pith, with high wood density and low vessel area, the relationship between the two variables is linear (R 2 = -32.1%, P\0.01) but with increasing tree age and vessel size, the wood density remains rather constant, suggesting that decreases in density might compromise mechanical support of the tree at a stage when the increase in crosssectional area alone might not provide mechanical stability. Other anatomical characteristics not considered in this study, like large xylem rays that increase with cambial age, may be responsible for the constant density
Keywords: Cork oak; Quercus suber; vessels; wood anatomy; Wood density

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V.; Castro-Díez, P.; Valladares, F. (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V; Castro-Diez, P; Valladares, F (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy

Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) - Caneva, G; Galotta, G; Cancellieri, L; Savo, V (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.
Keywords: archaeological site; catacombs; hypogeal conservation; rome; tree roots and buildings; Trees; wood anatomy

Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) - Caneva, G.; Galotta, G.; Cancellieri, L.; Savo, V. (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: archaeological site; catacombs; hypogeal conservation; rome; tree roots and buildings; Trees; wood anatomy

Cork oak (Quercus suber L.) wood growth and vessel characteristics variations in relation to climate and cork harvesting - Leal, Sofia; Nunes, Elsa; Pereira, Helena (European Journal of Forest Research, 2007)
Variations in tree ring growth of Quercus suber L. were analysed using dendrochronological techniques on cork oak discs from trees harvested in the cork producing region of Alentejo, Portugal. A tree-ring chronology containing a strong common signal and covering the period from 1970 to 1995 was build for ca. 30-year-old cork oaks never submitted to cork harvesting using 14 trees that crossdated satisfactorily out of 30 sampled trees. The tree ring indices correlated positively with September temperature (r = 0.48, P < 0.05) and very strongly with precipitation totals from previous October until current February (r = 0.82, P < 0.001) showing that the water stored in the soil during the autumn and winter months prior to the growing season has a primordial effect on the growth of the given season. The effects of cork harvesting were analysed by comparing mean ring width, mean annual vessel area, vessel density (nvessels/mm 2 ), and vessel coverage (percentage of transverse surface occupied by vessels) between three mature cork oak trees and three young trees, for the period from 1987 to 1996, corresponding to the growth between two consecutive cork removals in the case of mature trees. In 1988, 1989 and 1996 (corresponding to the ﬁrst and second years after cork removal, and 1996 to a year of cork removal), the ratios between ring widths of young versus mature trees was twice that for the rest of the period. However, an effect of cork removal indicated by eventual alterations in vessel size and distribution in the wood rings corresponding to the years 1988, 1989 and 1996 in the mature cork oaks was not observed.
Keywords: cork harvesting; Dendrochronology; Precipitation; Quercus Suber L; tree rings; wood anatomy; wood vessels

Within and between-tree variation in the biometry of wood rays and fibres in cork oak (Quercus suber_L.) - Leal, Sofia; Sousa, Vicelina B; Pereira, Helena (Wood Science and Technology, 2006)
The variability of ﬁbre and ray dimensions was studied at three radial positions (10, 50 and 90% of radius) in 5 cork oaks (Quercus suber L.) approximately 40 years old. Uniseriate ray height and cell number as well as multiseriate ray height and width were measured in tangential sections. Fibre length, width and wall thickness were measured after maceration. The most striking features of cork oak wood were the large multiseriate rays and the frequent homocellular uniseriate rays. On average multiseriate rays were 5.16 mm high and 0.48 mm wide, and uniseriate rays contained 11 cells and were 227 lm high. Neighbour rays presented large dimensional diﬀerences but there was no radial variation and there were very small between-tree diﬀerences. The radial maintenance of high and wide rays was discussed as a means to improve water shortage in response to water stress. Fibre dimensions increased radially but diﬀered little between trees: on average, 960–1,220 lm length, 18.40–21.49 lm width and 6.66–8.07 lm wall thickness. The ray pattern showed enough variation for visual appreciation while ensuring within and between-tree uniformity. The presence of rays has to be taken into consideration for designing wood drying programs.
Keywords: Cork oak; fibre biometry; wood anatomy; wood rays (PG)

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L; Tognetti, Roberto; Bräker, Otto U; Schoch, Werner; Innes, John L (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L.; Tognetti, Roberto; Bräker, Otto U.; Schoch, Werner; INNES, JOHN L. (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
The following values have no corresponding Zotero field: accession-num: 12620063
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Stem xylem features in three Quercus (Fagaceae) species along a climatic gradient in NE Spain - VILLAR-SALVADOR, P (Trees-Structure and …, 1997)
Stem xylem features in two evergreen Quercus species (Q. coccifera and Q. ilex) and a deciduous one (Q. faginea) were analysed along an Atlantic-Mediterranean climatic gradient in which rainfall and winter cold experi- ence strong variation. Mean maximum vessel diameter, vessel density, vessel element length, xylem transverse sectional area, Huber value (xylem transverse sectional area per leaf area unit), theoretical leaf specific conductiv- ity (estimated hydraulic conductance per leaf area unit) and total leaf area were determined in 3-year-old branches. Q. faginea presented the widest vessels and the highest theo- retical leaf specific conductivity while Q. coccifera showed the lowest total leaf area and the highest Huber value. Studied features did not exhibit significant correlations with mean minimum January temperature in any species but did show significant relationships with rainfall. In Q. coccifera, mean maximum vessel diameter, vessel element length and theoretical leaf specific conductivity increased with higher rainfall while vessel density decreased. Mean maximum vessel diameter and total leaf area in Q. ilex increased with precipitation whereas variables of Q. faginea did not show any significant trend. Results suggest that aridity, rather than minimum winter temperature, controls stem xylem responses in the studied evergreen species. Q. faginea traits did not show any response to precipitation, probably because this species develops deep roots, which in turn makes edaphic and topographic factors more important in the control of soil water availability. In response to aridity Q. coccifera only exhibits adjustment at a xylem level by reducing its water transport capacity through a reduction of vessel diameter without changing the amount of xylem tissue or foliage, whereas Q. ilex adjusts its water transport capacity in parallel to the foliage area.
Keywords: huber value; Mediterranean climate; rainfall gradient; winter temperature; wood anatomy

L'evoluzione della cerchia legnosa in Quercus Pubescens W. Ein Quercus Ilex L. nel clima di Firenze - Maugini, Elena (Giornale botanico italiano, 1950)
Summary The evolution of the wood ring in Quercus pubescens W. and in Quercus Ilex L. in Florence (from June 1946 to June 1947). The present study deals with the anatomical characters of the wood ring of Q. pubescens and of Q. Ilex. In both the specimens the wood of the stem and of the young branch has been investigated. In both plants studied the cambial tissue of the stem starts dividing at the end of April, reaching its maximum activity from May to June. On the contrary the cambium of the branch differentiates in Q. pubescens a month earlier (18 March-18 April) than in Q. Ilex (18 April-18 May). While in the branch of Q. Ilex a false ring can be seen corresponding to the autumn months, nothing of the kind is found in the branch of Q. pubescens; though it presents a false ring in the stem. It is difficult to date clearly the period when the cambium stops its activity, but probably it happens at the end of August in the samples of the stem. The leaf buds of Q. pubescens and of Q. Ilex open during April-May and the young branch is completely developed at the end of June. In both oaks some buds open in autumn, but the small branches are prevented to develop because of the cold. No comparison can be made between the opening of the buds and the beginning of the cambial activity in the stem and in the branch. Considering the evolution of these woods and their relationship to climatic factors, we can see that the cambial activity starts during a period of remarkable rainfall and of regular increase of temperature, and stops almost completely at the end of July, when temperature and dryness reach their highest values. The autumn rainfall would favour again a cambial activity, but the values of the temperature, regularly decreasing, do not allow it.
doi: 10.1080/11263505009431489
Keywords: Quercus ilex; Quercus pubescens (PG); wood anatomy; wood rings